DUKUNGAN SEBAYA DENGAN HARGA DIRI WANITA USIA SUBUR YANG TERINFEKSI HIV - Nengah Runiari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
This study aims to determine the association of peer support and self-esteem of childbearing-age women with HIV at The Spirit Paramacitta Foundation. The research design used a correlational design and cross-sectional approach using purposive sampling. The sample size was 57 people. A support questionnaires and RSES questionnaires were used to collect the data. The results showed that 27 childbearing-age women (47.4%) who were infected with HIV have gotten good support and 45 (78.9%) respondents had high self-esteem. Chi-Square analysis was performed to test the hypothesis and resulting 0.000 of p-value (alpha = 0.05), which implies that there is a significant association between support form peer supporters and self-esteem in women of childbearing age with HIV.